(untitled) (Hekima Review, 2007)
An examination of the seven passages shows that two references are found in narratives which have parallels in Luke’s gospel. These can therefore be considered as a Matthaean rework of Q material. In these two instances, the reworking consists precisely in bringing into the Q material the concept of righteousness. That is the case of Mt 5:6 (“Blessed are those who hunger and thirst for righteousness, for they will be filled”), whereas Lk 6:21 simply reads: “Blessed are you who are hungry now, for you will be filled,” and of Mt 6:33(“Strive first for the kingdom of God and its righteousness”), Lk 12:31 has simply: “Seek his kingdom and these things shall be yours as well.” The other references (3:15, 5:10, 5:20, 6:1, 21:32) are peculiar to Matthew’s redactional economy and can be considered as M material.